Examining the Nature and Extent of Hazing at Five NCAA Division III Institutions and Considering the Implications for Prevention - Kerschner, David; Allan, Elizabeth (Journal of Amateur Sport, 2021)
Building on the scholarship of Hoover (1999) and Allan and Madden (2008, 2012), we examined the nature and extent of hazing at five NCAA Division III institutions. NCAA Division III athletics has not been a focus of scholarly inquiry on the subject of hazing, despite documented accounts of athletes experiencing hazing and the outsized impact varsity athlete hazing can have on campus climate, given the high percentage of the student body at Division III institutions that may be at risk. Across the five institutions in this study, 40.9% of athletes experienced hazing, compared to 24.8% of non-athletes. The percentage of athletes that experienced hazing at the five Division III institutions ranged from 19.6% to 56.5%. Athletes experienced high-risk and abusive behaviors and were more likely than their non-athlete peers to have attitudes and perceptions supportive of hazing. These results indicate there is a need for research-informed hazing prevention strategies that can be utilized by Division III colleges and universities. Researchers can build upon these findings by continuing to examine hazing and factors predictive of hazing across institutional type within NCAA Division III.